The Elusive Antifibrotic Macrophage - Adhyatmika, Adhyatmika; Putri, Kurnia S. S.; Beljaars, Leonie; Melgert, Barbro N. (Frontiers in Medicine, 2015)
Fibrotic diseases, especially of the liver, the cardiovascular system, the kidneys, and the lungs account for approximately 45% of deaths in Western societies. Fibrosis is a serious complication associated with aging and/or chronic inflammation or injury and cannot be treated effectively yet. It is characterized by excessive deposition of extracellular matrix (ECM) proteins by myofibroblasts and impaired degradation by macrophages. This ultimately destroys the normal structure of an organ, which leads to loss of function. Most efforts to develop drugs have focused on inhibiting ECM production by myofibroblasts and have not yielded many effective drugs yet. Another option is to stimulate the cells that are responsible for degradation and uptake of excess ECM, i.e. antifibrotic macrophages. However, macrophages are plastic cells that have many faces in fibrosis, including profibrotic behaviour stimulating ECM production. This can be dependent on their origin, as the different organs have tissue-resident macrophages with different origins and a various influx of incoming monocytes in steady-state conditions and during fibrosis. To be able to pharmacologically stimulate the right kind of behaviour in fibrosis, a thorough characterization of antifibrotic macrophages is necessary, as well as an understanding of the signals they need to degrade ECM. In this review we will summarize the current state of the art regarding the antifibrotic macrophage phenotype and the signals that stimulate its behaviour.